2015
DOI: 10.1097/nor.0000000000000177
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Patient-Centered and Family-Centered Care Experience of Total Joint Replacement Patients Using a Shadowing Technique

Abstract: In 2030, when baby boomers reach 65 years of age and represent 18% of the population, it is anticipated that 67 million adults will have a diagnosis of arthritis increasing the demand for total hip and knee arthroplasty. With the growing emphasis on patient- and family-centered care, the aim of this project was to assess the patient experience of patients and families throughout the entire spectrum of the total joint replacement service line care at a university regional trauma hospital. A shadowing methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 4 publications
1
18
0
Order By: Relevance
“…Use of shadowing as a technique to examine the real-time care experience provides valuable data on process flow, patient experience, and team communication. Seeing care through the eyes of the patient allows for an assessment of the current state and development of improved processes that are grounded in information provided by patients and families ( DiGioia & Greenhouse, 2011 ; Marcus-Aiyeku et al, 2015 ). Combining shadowing data with Lean Six Sigma methodology or with rapid-cycle improvement processes is an approach for ongoing quality improvement that must be integrated into role expectations of the professional care team.…”
Section: Nursing's Role In the New Healthcare Arenamentioning
confidence: 99%
“…Use of shadowing as a technique to examine the real-time care experience provides valuable data on process flow, patient experience, and team communication. Seeing care through the eyes of the patient allows for an assessment of the current state and development of improved processes that are grounded in information provided by patients and families ( DiGioia & Greenhouse, 2011 ; Marcus-Aiyeku et al, 2015 ). Combining shadowing data with Lean Six Sigma methodology or with rapid-cycle improvement processes is an approach for ongoing quality improvement that must be integrated into role expectations of the professional care team.…”
Section: Nursing's Role In the New Healthcare Arenamentioning
confidence: 99%
“…Patient shadowing may have an especially valuable role in gaining insights into complex cross-hospital processes, in particular when dealing with vulnerable people who could be excluded from interview studies [26, 27]. Furthermore, some studies have reported how, through shadowing methodology, it is possible to assess the lived experience of patients in a patient-centred perspective [28, 29]. However, methodological and ethical issues of shadowing still need to be explored in greater depth [25, 30].…”
Section: Introductionmentioning
confidence: 99%
“…Continued skyrocketing of healthcare costs, less than impressive heath status of the American people, safety and quality issues within the healthcare system, growing concerns that cost and quality issues would intensify with changing demographics, and the reality that there were 50 million Americans uninsured and 40 million underinsured in the United States ushered in the Patient Protection and Affordable Care Act of 2010 ( Salmond, 2015 ). The Affordable Care Act (ACA) is more than insurance reform and greater access for the newly insured but includes programs now led by the CMS aiming to improve quality and control costs-what is being termed value.…”
Section: Enter Healthcare Reformmentioning
confidence: 99%
“…Use of shadowing as a technique to examine the real-time care experience provides valuable data on process fl ow, patient experience, and team communication. Seeing care through the eyes of the patient allows for an assessment of the current state and development of improved processes that are grounded in information provided by patients and families ( DiGioia & Greenhouse, 2011 ;Marcus-Aiyeku et al, 2015 ). Combining shadowing data with Lean Six Sigma methodology or with rapid-cycle improvement processes is an approach for ongoing quality improvement that must be integrated into role expectations of the professional care team.…”
Section: Data Analytics: a Focus On Outcomes And Improvementmentioning
confidence: 99%
See 1 more Smart Citation